A Morphological Analysis Of Derivational Suffixes Of NounIn Manual Procedure Of Blackberry Guide - Maharani, Ghisma Ovilia; , Drs. Sigit Haryanto, M.Hum; , Dr. Dwi Haryanti, M.Hum (2014)
This research paper elaborates a morphological study of derivational suffixof noun in manual procedure guide blackberry. The objectives of the research are to describe the types of derivational suffix of noun and analyze the meaning of words using suffixes in Manual Procedure Guide Blackberry. The researcher employs the descriptive qualitative research as the type of the research. The data source is manual procedure guide blackberry. The techniques of collecting data is reading the manual procedure guide blackberry, identifying data all words contain derivational suffix of procedure guide blackberry, classifying data with some categories of the type derivational suffix of noun, and the meaning of derivational suffix of noun. The result of the study are as follows. First the types of noun derivational suffixes and all words using suffixes in manual procedure guide blackberry. The suffix are: -ing, -er, -ant, -cation, -ion, -ice, -ation, -ator, -ed, -ive.The suffix above can change word class from verb into noun, adjective into noun, adveb into noun. For example typing, understanding, user, player, application, navigation, spesification.Second is the meaning of derivational suffixes of noun, the writer found 201 data in manual procedure guide blackberry with the suffix ing, -er, - ant, -cation, -ion, -ice, -ation, -ator, -ed, -ive, and combines with the words there are availability, capability. The example words using suffixes are: server, provider, specification, information, dependant, declaration, servis, administrator, offering, broadcasting, forwarding, intruction, directive, and combinewith two words availability, capability